Pengembangan E-booklet Bernuansa Emotional Spiritual Quotient Tentang Materi Sistem Reproduksi Manusia untuk Peserta Didik Fase F: Penelitian - Cemara; Zulyusri; Fitri Olvia Rahmi; Rya Anggriyani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to develop an e-booklet with an Emotional Spiritual Quotient (ESQ) theme on human reproductive system material for high school/Islamic high school students in Phase F. The development was carried out using the 4D model (Define, Design, Develop, Disseminate) with the dissemination stage not realized due to constraints in available time and budget. The background of the research is the low strengthening of character, especially emotional and spiritual intelligence, in biology learning. The product was validated by two Biology lecturers and one Biology teacher, while practicality was tested by one teacher and 30 Phase F students at SMAN 1 Lubuk Basung. The results of this study show that the validity score reached 94.93% (very valid) and the average practicality score was 95.92% (very practical).